The Measurement of Islamic Bank Performance: A Study Using Maqasid Index and Profitability - Aam Rusydiana; Salman Al Parisi (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2016)
This study aims to 1) measure Syariah Maqasid Index (SMI) and Profitability Index (PI) of Islamic Banks, and 2) compare the Syariah Maqasid and Profitability Index of Islamic Banks during 2011-2014 with cartesian diagram. This research consists of 2 methods: syariah maqasid index weighting (sekaran method), and Comparative Performance Index (CPI). The object of research consist of 11 Islamic Banks (BUS) in Indonesia with annual data 2011 to 2014. Result: Syariah Maqasid Index of BUS during 2011-2014 from the highest to the lowest, namely Panin Syariah (0254), BCAS (0212), BMI (0208), BRIS (0207), BSM (0202), BSB (0.2008), BJBS ( 0.2006), Victoria Syariah (0199), Maybank Syariah (0197), BNIS (0195), Mega Syariah Bank (0172). Then Profitability Index of BUS in 2011-2014 from the highest to the lowest, namely Maybank Syariah (628.5), Bank Mega Syariah (472.1), BSM (459.9), Panin Syariah (395.5), Victoria Sharia (355.4), BNIS (252.6), BMI (218.2), BCAS (155.4), BSB (150.9), BRIS (135.3), and BJBS (122.3). Conclusion: The highest of Syariah Maqasid Index is Panin Syariah Bank in period 2011-2014, while the highest of Profitability Index is Maybank Syariah in period 2011-2014.